2019
DOI: 10.1016/j.celrep.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Myelin-Specific Th17 Cell Gut Homing Confers Protection in an Adoptive Transfer Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis (MS) is a common autoimmune disease of the CNS. Although an association between MS and inflammatory bowel diseases is observed, the link connecting intestinal immune responses and neuroinflammation remains unclear. Here we show that encephalitogenic Th17 cells infiltrate the colonic lamina propria before neurological symptom development in two murine MS models, active and adoptive transfer experimental autoimmune encephalomyelitis (EAE). Specifically targeting Th17 cell intestinal homing by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 64 publications
7
46
1
Order By: Relevance
“…Given its role in shaping the host immune response, among other physiological processes, significant effort has been devoted to investigating the role of the gut microbiota in MS. Lactobacillus sp. has been found to be significantly depleted in MS patients compared to controls [ 2 , 3 ], mirroring what we and others have observed in EAE [ 7 , 11 ]. Recently, it has been shown that myelin-specific T helper (Th)17 cells proliferate in the gut prior to the development of neurological symptoms in EAE and are associated with a decrease in gut-derived Lactobacillus [ 11 ].…”
Section: Discussionsupporting
confidence: 89%
“…Given its role in shaping the host immune response, among other physiological processes, significant effort has been devoted to investigating the role of the gut microbiota in MS. Lactobacillus sp. has been found to be significantly depleted in MS patients compared to controls [ 2 , 3 ], mirroring what we and others have observed in EAE [ 7 , 11 ]. Recently, it has been shown that myelin-specific T helper (Th)17 cells proliferate in the gut prior to the development of neurological symptoms in EAE and are associated with a decrease in gut-derived Lactobacillus [ 11 ].…”
Section: Discussionsupporting
confidence: 89%
“…Considering that the expression of Tlr4 is low at the small intestine in a steady-state condition 73 , we believe that most of its elevated expression in EAE mice could be due to the presence of inflammatory cells, mainly CD4 + T lymphocytes and γδT cells. This possibility is supported by data that indicates a T cell homing stage during EAE development 33,72 . In the EAE model, the absence of TLR4 solely in CD4 + T cells significantly decreased disease signs; the authors also found that Tlr4 -/-γδT cells presented defective IFN-γ and IL-17 production 74 .…”
Section: Discussionsupporting
confidence: 56%
“…Notably, we also detected the presence of yeasts in both treated groups (as indicated in the upright insert in the third panel) suggesting, therefore, their gut accumulation after treatment. Gut-homing of myelin-specific Th17 has been described as a pivotal step for the development of EAE 33 . Assays involving gene expression in intestinal samples and cytokine production by gut explant cultures were then performed to evaluate if supplementation was affecting the local level of T cell subsets, including Th17 and Treg, and of immunoregulatory molecules.…”
Section: Selemax Controls Intestinal Inflammation Better Than S Cerementioning
confidence: 99%
“…Oligodendrocytes, the myelin-producing cells of the CNS, are the main ACE2 + TMPRSS2 + cell type in the brain, the myelin transcriptional regulator MYRF was enriched in certain ACE2 + TMPRSS2 + cell types as noted above, and myelin proteins MOG and MBP were coexpressed in numerous ACE2+ clusters across organs. MYRF and MBP were significantly differentially expressed in ACE2 + TMPRSS2 + subsets of the lung and gut ( Supplementary Table 10); myelin targeting Th17 cells trained in the gut are able to infiltrate the CNS in a mouse model of experimental autoimmune encephalomyelitis 143 . Taken together, the expression of myelin proteins across multiple ACE2 + TMPRSS2 + cells may hypothetically contribute to antigen presentation and autoimmune response in the context of viral infection.…”
Section: Discussionmentioning
confidence: 99%